2003
DOI: 10.1002/ejoc.200300222
|View full text |Cite
|
Sign up to set email alerts
|

Highly Enantioselective Rhodium‐Catalyzed Hydrogenation of 2‐(2‐Methoxy‐2‐oxoethyl)acrylic Acid − A Convenient Access of Enantiomerically Pure Isoprenoid Building Blocks

Abstract: Asymmetric catalytic hydrogenation of 2‐(2‐methoxy‐2‐oxoethyl)acrylic acid (5) to give (2S)‐4‐methoxy‐2‐methyl‐4‐oxobutanoic acid [(S)‐6] was studied. An enantiomeric excess of 99.7% ee was achieved with a catalyst formed in situ from [Rh(COD)2]BF4 and the chiral phosphite L2 in 1,2‐dichloroethane as solvent. In addition, enzyme‐catalyzed semi‐saponification of dimethyl 2‐methylsuccinate was investigated. Mono ester (S)‐6 was transformed into a few compounds which can serve as C5‐building blocks in natural pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…[a] [72] tert-Butyl(2-iodoethoxy)diphenylsilane: A solution of 2-iodoethanol (10.0 g, 58 mmol), TBDPSCl (17.9 mL, 69.8 mmol) and imidazole (4.7 g, 69.8 mmol) in CH 2 Cl 2 (70 mL) was stirred for 18 h. Water (30 mL) was added and the mixture extracted with CH 2 Cl 2 (2 30 mL), the combined organic phases were dried over Na 2 SO 4 and evaporated, and the crude material purified by flash chromatography (hexanes) to yield the title compound as a white solid (23.0 g, 97 %). Compound 36: nBuLi (1.6 m solution in hexane, 5.6 mL, 8.9 mmol) was added to a suspension of flame-dried LiCl (806 mg, 19.2 mmol) and iPr 2 NH (1.3 mL, 0.96 mmol) in THF at 0 8C.…”
Section: Resultsmentioning
confidence: 99%
“…[a] [72] tert-Butyl(2-iodoethoxy)diphenylsilane: A solution of 2-iodoethanol (10.0 g, 58 mmol), TBDPSCl (17.9 mL, 69.8 mmol) and imidazole (4.7 g, 69.8 mmol) in CH 2 Cl 2 (70 mL) was stirred for 18 h. Water (30 mL) was added and the mixture extracted with CH 2 Cl 2 (2 30 mL), the combined organic phases were dried over Na 2 SO 4 and evaporated, and the crude material purified by flash chromatography (hexanes) to yield the title compound as a white solid (23.0 g, 97 %). Compound 36: nBuLi (1.6 m solution in hexane, 5.6 mL, 8.9 mmol) was added to a suspension of flame-dried LiCl (806 mg, 19.2 mmol) and iPr 2 NH (1.3 mL, 0.96 mmol) in THF at 0 8C.…”
Section: Resultsmentioning
confidence: 99%
“…All the microbes were found to be sensitive towards compound 20 displaying MIC values 2.12-2.32 µg/mL. The study also showed that halogenated esters (12)(13)(14)(15)(16)(17)(18)(19) (1-8, 21-29) microbes were resistant and showed very small zone of inhibition (Table 1), whereas compounds 9-11 were almost inactive. The prepared compounds showed interesting structure activity relationships while exploring their antifungal and antibacterial activity.…”
Section: Resultsmentioning
confidence: 84%
“…Relatively high activity was observed for compounds with substituent at 2 and 4 position of benzene ring. Highest activity was revealed by halogenated monoesters (12)(13)(14)(15)(16)(17)(18)(19)(20) in general and iodinated monoesters in particular (18)(19)(20). Monoesters having substituents linked through oxygen to benzene ring (1)(2)(3)(4)(5)(6)(7)(8) and (24-29) displayed relatively less activity as compared to halogenated monoesters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] These bifunctional, enantiomerically pure compounds could thus be transformed into useful building blocks for a range of (pharmaceutically relevant) natural products. [3] Surprisingly, the use of such itaconic acid monoesters in asymmetric hydrogenation research has received only moderate attention [4] and particularly examples of substrates with a carboxylic acid moiety in the conjugated position are rare. [3,4b,5] In addition, the asymmetric hydrogenation of substituted itaconate derivatives has remained relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%